How Instrumental is Organizational Agility Toward Sustainable Human Resource Management During the VUCA Situation - Ratri Buda Nugrahanti; Tantri Widiastuti (Jurnal Ekonomi Manajemen Akuntansi, 2024)
The COVID-19 pandemic caused volatility, uncertainty, complexity, and ambiguity (VUCA), and has created an unprecedented change for all organizations to either evolved or seized to exist. The dynamism due to COVID-19 has forced the HRM function to look forward to organizational agility to adapt and stay in business. The approach to make a linkage between COVID-19, organizational agility, and sustainable HRM is theoretically argued based on a resource-based theory. By conceptualizing the work of Dyer & Shafer (2014) and Nijssen & Paauwe (2012) five dimensions are identified to measure organizational agility, which includes fluid organizational design, flexible core business strategy, distributive information, fast organizational learning, and highly adaptable infrastructure and workplace design. However, further research is needed to confirm the dimensions proposed and to expand them into indicators that can specifically measure organizational agility as a variable.